Transference of 3D accelerations during cross country mountain biking - Macdermid, P. W.; Fink, P. W.; Stannard, S. R. (Journal of Biomechanics, 2014)
Investigations into the work demands of Olympic format cross country mountain biking suggest an incongruent relationship between work done and physiological strain experienced by participants. A likely but unsubstantiated cause is the extra work demand of muscle damping of terrain/surface induced vibrations. The purpose of this study was to describe the relationship between vibration mechanics and their interaction with terrain, bicycle and rider during a race pace effort on a cross country mountain bike track, on both 26´ and 29´ wheels. Participants completed one lap of a cross country track using 26´ and 29´ wheels, at race pace. Power, cadence, speed, heart rate and geographical position were sampled and logged every second for control purposes. Tri-axial accelerometers located on the bicycle and rider, recorded accelerations (128Hz) and were used to quantify vibrations experienced during the whole lap and over terrain sections (uphill and downhill). While there were no differences in power output (p=0.3062) and heart rate (p=0.8423), time to complete the lap was significantly (p=0.0061) faster on the 29´ wheels despite increased vibrations in the larger wheels (p=0.0020). Overall accelerometer data (RMS) showed location differences (p<0.0001), specifically between the point of interface of bike-body compared to those experienced at the lower back and head. The reduction in accelerations at both the lower back and head are imperative for injury prevention and demonstrates an additional non-propulsive, muscular, challenge to riding. Stress was greatest during downhill sections as acceleration differences between locations were greater when compared to uphill sections, and thus possibly prevent the recovery processes that may occur during non-propulsive load.